?TRAFFIC NOISE IN HVDERABAD CITY PART I.ROAD TRAFFIC NOISE - Shaikh, G H; Shaikh, Qameruddin (Biological Sciences - PJSIR, 2000)
Traffic noise survey was conducted at20 sites indifferent areasand localitiesin Hyderabadcity and ateach site noise data was collected continuously from 0800 to 2000 h .The data was analyzed for L L L L andL and approximate values of A99. A'JO. MO. AIO AI. LAeql2h were evaluated for each site. The results are discussed with reference to some criteria lor community annoyance and means and ways to limit high-level traffic noise are suggested.